Takbir ZawÄid dalam Salat Id Prespektif K.H. Lanre Said al-Bugisi - Syandri, Syandri; Saifullah bin Anshor; Patahuddin, Askar; Miranto, Agus (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
This research aimed to identify zawÄid takbir in id prayer according to K.H Lanre Said al-Bugisi perspective. This research was a qualitative descriptive study using the library research method with juridical-normative and philosophical approaches. The results of this study indicate that in determining shari law, K.H. Lanre Said used several approaches and methods. The method of iá¹£tishÄbul hÄl, muqaranÄt al-maáº“Ähib, tarjih, and the principle of